Crossing the Rubicon: the degree in Library and Documentation Science and the labor market - Blanco Domingo, Luis Mariano (Revista General de Información y Documentación, 2024)
The aim of this paper is to analyse the impact of the digital transformation and the new labour context on the contents taught in the Bachelor’s Degree in Information and Documentation, while at the same time offering some recommendations to adapt them to the reality of the labour market. To this end, a descriptive and prospective analysis of various information resources has been carried out, obtaining results that point to a serious decline in demand in the traditional field of memory institutions, while at the same time needs are increasing in fields more closely linked to content and data management, to the technological elements that support and make access to the knowledge society possible. The main conclusion is that it is essential that the teaching contents taught in the aforementioned Degree be updated, seeking on the one hand to attract a greater number of potential students, and on the other to adapt in a flexible way to the new digital realities that characterise the labour context, without this implying abandoning the more traditional elements linked to memory institutions. But the job market also demands professionals in metadata and standardisation, experts in collection development, subject specialists, experts in antiquarian collections, curators, experts in the management and preservation of digital collections, experts in bibliometrics and quantitative techniques, or in scientific publishing. New roles, new employment niches in constant expansion and evolution. We have evolved from document management as a hard core to a new offer of information management and more transversal profiles.